2017
DOI: 10.1136/tobaccocontrol-2016-053602
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence that high levels of nicotine on children’s hands may contribute to overall tobacco smoke exposure

Abstract: Background Dust and surfaces are important sources of lead and pesticide exposure in young children. The purpose of this pilot study was to investigate if third-hand smoke (THS) pollutants accumulate on the hands of children who live in environments where tobacco is used and if hand nicotine levels are associated with second-hand smoke (SHS), as measured by salivary cotinine. Methods Participants were parents and children (n=25; age mean (SD)=5.4 (5.3) years) presenting to the emergency department with a pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 14 publications
5
51
0
3
Order By: Relevance
“…of tobacco smoke has been extinguished) can accumulate on surfaces, becoming progressively more toxic, and can contribute to overall tobacco smoke exposure (166)(167)(168). New research demonstrated that components of THS can exacerbate a mouse asthma model through mast cells, resulting in airway inflammation and remodeling (168).…”
Section: Resultsmentioning
confidence: 99%
“…of tobacco smoke has been extinguished) can accumulate on surfaces, becoming progressively more toxic, and can contribute to overall tobacco smoke exposure (166)(167)(168). New research demonstrated that components of THS can exacerbate a mouse asthma model through mast cells, resulting in airway inflammation and remodeling (168).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that adolescents who live with smokers who do not smoke inside the home are still potentially exposed to tobacco smoke and its related toxicants. 26 Despite an overall recent decline in TSE, 2 we highlight the need for continued TSE reduction initiatives, especially for adolescents, nationwide.…”
Section: Discussionmentioning
confidence: 96%
“…THS consists of nicotine‐containing residues or old tobacco smoke particles. It adheres to surfaces of the home and the clothing of caregivers after the consumption of tobacco and is absorbed by ingestion, skin, or inhalation by children 4 …”
Section: Introductionmentioning
confidence: 99%
“…It adheres to surfaces of the home and the clothing of caregivers after the consumption of tobacco and is absorbed by ingestion, skin, or inhalation by children. 4 The home is the greatest single source of ETS for children, who are most susceptible population to the harmful effects of ETS. 5 Questionnaires have been the methods commonly used to assess ETS exposure.…”
Section: Introductionmentioning
confidence: 99%